Uma Iconografia Profética Da Restauração: A Imagem De Ourique E As Disputas Políticas Nas Gravuras De 1632 A 1668. - Sanchez, Talita De Jesus Noronha [UNIFESP] (2018)
Based On The Narratives Of The Ourique"S Miracle And The Visual Circulation Of Afonso Henriques"S Oath, This Dissertation Aims To Analyze The Mechanisms Of Political Expression During The Restoration Of Portugal, Especially Focusing On The Visual Medium. By Using The Notion Of Communicative Trinity (Bouza-Álvarez) And A Historiographical Debate On The Impacts Of The Restoration During The 17th Century (Between Rafael Valladares, Bouza-Álvarez, Oliveira França And Schaub), This Research Studied The Iconography From 1632 To 1668. For This Purpose, Engravings In Texts With Restorative Content Were Selected In Order To Identify The Constant Reference To Prophetic Formulations, Which Legitimated The House Of Braganza"S Royal Power In The Visual Production Of The Period. It Was Possible To Notice The Role Played By The Images In Political-Prophetic Discourses " Evincing The Emblematic Aspect Of The Engravings During The Restoration; To Map The Topoi Utilized In These Compositions; And To Highlight The "Images War"